Proflavine/acriflavine derivatives with versatile biological activities - Sabolova, Danica; Kristian, Pavol; Kozurkova, Mária (JAT. Journal of applied toxicology, 2020)
Proflavine derivatives are extremely interesting chemotherapeutic agents, which have shown promising pharmaceutical potential due to their wide range of biological activities. This review summarizes the current state of research into the anticancer, antimicrobial, antimalarial and antileishmanial properties of these attractive compounds. Our attention has focused on new classes of proflavine conjugates, which display significant levels of anticancer activity. Highly promising cytotoxic properties have been identified in proflavine conjugates with imidazolidinones, ureas and thioureas. In particular, proflavine-dialkyldithioureas displayed substantial cytotoxic effect against the human leukemia HL-60 cells with IC50 values from 7.2 to 34.0 μm. As well, palladium complexes with proflavine ligand have important biologic activity. The LC50 values of these complexes were significantly lower than that of cisplatin against the SK-BR-3 cell line.
Keywords: akriflavin; proflavin; protinádorové látky; Structure-Activity Relationship; Proflavine; molekulární struktura; Molecular Structure; vztah mezi dávkou a účinkem léčiva; Acriflavine; Inhibitory Concentration 50; Anti-Infective Agents; vztahy mezi strukturou a aktivitou; Animals; lidé; Humans; zvířata; inhibiční koncentrace 50; antiinfekční látky; Dose-Response Relationship, Drug; Antineoplastic Agents